Effects of a Severe Mountain Pine Beetle Epidemic in Western Alberta, Canada under Two Forest Management Scenarios - Richard R. Schneider; Maria Cecilia Latham; Brad Stelfox; Dan Farr; Stan Boutin (International Journal of Forestry Research)
We used a simulation model to investigate possible effects of a severe mountain pine beetle (Dendroctonus ponderosae Hopkins) epidemic under two management scenarios in Alberta, Canada. Our simulated outbreak was based on the current epidemic in British Columbia, which may kill close to 80% of the province's pine volume. Our two management scenarios were conventional harvest and a pine-reduction strategy modeled on a component of Alberta's Mountain Pine Beetle Management Strategy. The pine strategy seeks to reduce the number of susceptible pine stands by 75% over the next 20 years through targeted harvesting by the forest industry. Our simulations showed that the pine strategy could not be effectively implemented, even if the onset of the beetle outbreak was delayed for 20 years. Even though we increased mill capacity by 20% and directed all harvesting to high volume pine stands during the pine strategy's surge cut, the amount of highly susceptible pine was reduced by only 43%. Additional pine volume remained within mixed stands that were not targeted by the pine strategy. When the outbreak occurred in each scenario, sufficient pine remained on the landscape for the beetle to cause the timber supply to collapse. Alternative management approaches and avenues for future research are discussed.